Comparison of X-ray Evidence of Marine Manganese Nodules and Non-marine Manganese Ore Deposits - Rudolf Giovanoli; Peter Bürki (CHIMIA)
X-ray diffraction evidence of manganese nodules confirm earlier reports on the presence of more or less finely divided buserite (10 Å phase), birnessite (7 Å phase), and random stacked birnessite. The iron bearing phase is most probably ferrihydrite, i,e. “amorphous” FeOOH. Non-marine manganese ores of similar composition except for iron, hitherto accepted as a defined mineral species “ todorokite ”, are buserite partly dehydrated to birnessite and partly reduced to manganite γ-MnOOH.